Laporan Keuangan untuk Mengukur Kinerja Keuangan Berdasarkan Rasio Likuiditas dan Solvabilitas pada PDAM Prabujaya Kota Rabumulih - Mufida Amaliah (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This research aims to determine the liquidity and solvency ratios to measure financial performance at PDAM in Prabumulih. This research uses types of quantitative descriptive research. This research uses a descriptive method to describe research objects or research results. The data in this research was collected through documentation, observation, and methods of interviews. The research results show the liquidity ratio, calculated from the analysis of PDAM Tirta Prabujaya City Prabumulih’s current ratio and quick ratio for 3 (three) last year, was good. Because the amount of current assets available is huge while the amount of current liabilities is small, this can be seen in the ratio value Liquidity in 2020, 2021 and 2022. The value of the Current Ratio is 8.08 times, 7.48 times and 6.24 times; the value of the Quick Ratio is 6.39 times, 5.78 times and 5.23 times, and the Cash Ratio values are 96%, 30% and 17%. Solvency Ratio, the overall financial performance of PDAM Tirta Prabujaya Prabumulih City during the last 3 (three) years it has been in good condition because its total assets and the company's available capital is greater than the total debt it has company. This can be seen in the 2020, 2021 and 2022 ratio values. The value of Debt to Assets Ratio of 54%, 38% and 69%. Next, the Debt to Equity, Ratio values of 92%, 23% and 94%.